A modeling and comparative study of bottom pressure signals generated by waves and ship in shallow water. (1st November 2022) - Deng, Hui; Wang, Ke-bin; Zhang, Zhi-hong; Yi, Wen-bin; Wang, Chong
Abstract: For the bottom pressure signal generated by an advancing ship in the ocean, the bottom pressure signal generated by waves is a strong background disturbance. Aiming at the differences between their characteristics, the modeling methods for predicting the bottom pressure signals generated by ship and waves in shallow water are presented and validated, meanwhile, their characteristics in time and frequency domains are simulated, compared, and analyzed. The findings clearly show that their characteristics differ in some key parameters, such as the pressure spectrum, the pressure peak, and the negative duration, etc. The modeling and comparative studies proposed in this paper are very beneficial for the design of underwater weapons, and helpful for identifying whether the target is indeed a ship or just an ocean environment interference. Highlights: A modeling method for predicting the bottom pressure signal generated by ship is proposed and validated. A modeling method for predicting the bottom pressure signals generated by waves is proposed and validated. The pressure spectrum and pressure-time characteristics generated by ship and waves are simulated and analyzed. A detail comparison between the characteristics of bottom pressure signal generated by ship and waves is presented.